Advances in two-photon absorption photodynamic therapy of glioma based on porphyrin-based metal-organicframework composites - Yong-Tao Gao; Jun-Hui Liu; Kang He; Shuang-lei Guo (Photodiagnosis and Photodynamic Therapy)
Gliomas of the brain are characterised by high aggressiveness, high postoperative recurrence rate, high morbidity and mortality, posing a great challenge to clinical treatment. Traditional treatments include surgery, radiotherapy and chemotherapy; they also have significant associated side effects, leading to difficulties in tumour resection and recurrence. Photodynamic therapy has been shown to be a promising new strategy to help treat malignant tumours of the brain. It irradiates the tumour site at a specific wavelength to activate a photosensitiser, which selectively accumulates at the tumour site, triggering a photochemical reaction that destroys the tumour cells. It has the advantages of being minimally invasive, highly targeted and with few adverse reactions, and is expected to be well used in anti-tumour therapy. However, the therapeutic effect of traditional PDT is limited by the weak tissue penetration ability of photosensitiser, hypoxia and immunosuppression in the tumour microenvironment. This paper reviews the current research status on the therapeutic principle of photodynamic therapy in glioma and the mechanism of tumour cell injury, and also analyses the advantages and disadvantages of the current application in glioma treatment, and clarifies the analysis of ideas to improve the tissue penetration ability of photosensitizers. It aims to provide a feasible direction for the improvement of photodynamic therapy for glioma and a reference for the clinical treatment of deep brain tumours.